The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.ygyno.2019.12.025
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis of CA125 glycoforms in the monitoring and follow up of high grade serous ovarian cancer

Abstract: is a more sensitive indicator of tumor load than conventional CA125. • The nadir value of CA125-STn is a predictor of progression free survival. • The CA125-STn assay detects relapse more precisely than the conventional CA125 assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…CA-125 is a well-known biomarker, but its significance is still of interest to clinicians and researchers. Recently, the role of nadir CA-125 and its glycoforms have been assessed by Finnish authors 26 ; the results of their study may undermine the prognostic significance of nadir CA-125 26 . The impact of new therapies (PARP inhibitors, immunotherapy) on clinical significance of nadir CA-125 is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…CA-125 is a well-known biomarker, but its significance is still of interest to clinicians and researchers. Recently, the role of nadir CA-125 and its glycoforms have been assessed by Finnish authors 26 ; the results of their study may undermine the prognostic significance of nadir CA-125 26 . The impact of new therapies (PARP inhibitors, immunotherapy) on clinical significance of nadir CA-125 is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is currently in use as an adjunct to diagnosis, in the monitoring of response to therapy, detection of recurrence of disease and determination of prognosis in EOC. Although a nonspecific marker of disease, it has been found to be elevated in 50% of women with early stage EOC and 80% of women with advanced disease [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…7,8 CA 125 levels are often used to evaluate treatment response in patients diagnosed with epithelial ovarian cancer especially HGSC. 9,10 Previous studies have investigated the significance of CA 125 level at the time of diagnosis. [11][12][13] Those studies showed that CA 125 levels were predictive of survival among patients with epithelial ovarian cancer, but outcomes are still unclear.…”
Section: 5mentioning
confidence: 99%